2023
DOI: 10.1093/mnras/stad1917
|View full text |Cite
|
Sign up to set email alerts
|

Star cluster formation and feedback in different environments of a Milky Way-like galaxy

Abstract: It remains unclear how galactic environment affects star formation and stellar cluster properties. This is difficult to address in Milky Way-mass galaxy simulations because of limited resolution and less accurate feedback compared to cloud-scale models. We carry out zoom-in simulations to re-simulate 100–300pc regions of a Milky Way-like galaxy using smoothed particle hydrodynamics, including finer resolution (0.4M⊙ per particle), cluster-sink particles, ray-traced photoionization from O stars, H2/CO chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 122 publications
1
5
0
Order By: Relevance
“…It is particularly surprising that we see so little difference in surface densities between the arm and interarm regions, since a notable difference has often been observed in other studies (Colombo et al 2014;Sun et al 2020;Rosolowsky et al 2021;Koda et al 2023). We also note that the clouds in the bar of NGC 1313 mostly have less extreme properties than those in the arms, whereas other studies have often seen enhancements of the velocity dispersion, surface density, and pressure in bars galactic centers (Sun et al 2020;Rosolowsky et al 2021;Ali et al 2023). This may not be so surprising since Querejeta et al (2021) have reported large variations in the properties of molecular gas in bars, potentially because star formation in bars is episodic.…”
Section: Virializationsupporting
confidence: 54%
See 1 more Smart Citation
“…It is particularly surprising that we see so little difference in surface densities between the arm and interarm regions, since a notable difference has often been observed in other studies (Colombo et al 2014;Sun et al 2020;Rosolowsky et al 2021;Koda et al 2023). We also note that the clouds in the bar of NGC 1313 mostly have less extreme properties than those in the arms, whereas other studies have often seen enhancements of the velocity dispersion, surface density, and pressure in bars galactic centers (Sun et al 2020;Rosolowsky et al 2021;Ali et al 2023). This may not be so surprising since Querejeta et al (2021) have reported large variations in the properties of molecular gas in bars, potentially because star formation in bars is episodic.…”
Section: Virializationsupporting
confidence: 54%
“…Considering the comparisons of the bootstrapped KS and AD tests in the Appendix, some of the most significant differences among all the pairings for both tests are between the central region of NGC 7793 and the bar and interarm regions of NGC 1313, for almost every property, with the notable exception of surface density and freefall time. This is somewhat surprising since the bar of NGC 1313 encompasses that galaxy's own central region and galaxy centers usually have more extreme cloud properties (Donovan Meyer et al 2013;Colombo et al 2014;Sun et al 2020;Ali et al 2023;Koda et al 2023). One other notable difference from the KS and AD tests is that the southern arm of NGC 1313 has statistically significant shorter freefall times than all regions of NGC 7793.…”
Section: Intergalaxy Region Comparisonsmentioning
confidence: 99%
“…However, we note that star cluster survivability after gas expulsion is independent of the impact of the Galactic tidal field (Shukirgaliyev et al 2019). Hence, we expect the increase of isolated intermediate-and high-mass YSOs with time to be independent of Galactic location (although see Ali et al 2023).…”
Section: Clustering Properties Of the More-massive Ysos (M >mentioning
confidence: 81%
“…Similarly to the spiral arms, simulations of the bar region also suggest that cloud mergers are more frequent leading to the formation of more massive clouds (Renaud et al, 2013;Fujimoto et al, 2014). Renaud et al (2013) also highlight the role of resonances in channeling gas to the ends of the bar to form massive clouds and clusters (Renaud et al, 2015;Ali et al, 2023) (Figure 5). Most work on galaxy centres has focused on our on Galactic Centre.…”
Section: Environmentmentioning
confidence: 98%